2011
DOI: 10.1136/jmedgenet-2011-100262
|View full text |Cite
|
Sign up to set email alerts
|

Allelic hierarchy of CDH23 mutations causing non-syndromic deafness DFNB12 or Usher syndrome USH1D in compound heterozygotes

Abstract: One DFNB12 allele in trans configuration to an USH1D allele of CDH23 preserves vision and balance in deaf individuals, indicating that the DFNB12 allele is phenotypically dominant to an USH1D allele. This finding has implications for genetic counselling and the development of therapies for retinitis pigmentosa in Usher syndrome. ACCESSION NUMBERS: The cDNA and protein Genbank accession numbers for CDH23 and cadherin 23 used in this paper are AY010111.2 and AAG27034.2, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 52 publications
2
89
0
Order By: Relevance
“…In contrast, a recent study reported that one hypomorphic CDH23 allele in trans configuration to a null CDH23 allele preserves vision and balance in deaf individuals [28]. Moreover, no allelic variants of CDH23 that cause RP or vestibular dysfunction with normal hearing have been reported [1, 4, 5, 28]. These results indicate that hypomorphic CDH23 alleles are phenotypically dominant to null CDH23 alleles and that hearing is more affected by CDH23 mutations than vision or vestibular function.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, a recent study reported that one hypomorphic CDH23 allele in trans configuration to a null CDH23 allele preserves vision and balance in deaf individuals [28]. Moreover, no allelic variants of CDH23 that cause RP or vestibular dysfunction with normal hearing have been reported [1, 4, 5, 28]. These results indicate that hypomorphic CDH23 alleles are phenotypically dominant to null CDH23 alleles and that hearing is more affected by CDH23 mutations than vision or vestibular function.…”
Section: Discussionmentioning
confidence: 96%
“…Some compound heterozygotes with one functionally null allele and one hypomorphic allele of CDH23 have an Usher phenotype [1]. In contrast, a recent study reported that one hypomorphic CDH23 allele in trans configuration to a null CDH23 allele preserves vision and balance in deaf individuals [28]. Moreover, no allelic variants of CDH23 that cause RP or vestibular dysfunction with normal hearing have been reported [1, 4, 5, 28].…”
Section: Discussionmentioning
confidence: 99%
“…CDH23, contributing to Leber optic atrophy and the three close diseases, is underlying the genetic overlap of 171 disease pairs; COL7A1, contributing to ARMD1 and the three close diseases, is underlying the genetic overlap of 1085 disease pairs. Mutations within both genes are shown in the literature (Schultz et al, 2011;Dighiero et al, 2004) to potentially cause vision loss. In contrast, the 32 genes underlying the genetic overlap of cataract, RP, and CBD include genes that are more specific to the three diseases, therefore contributing more significantly to their genetic overlap.…”
Section: Genetic Overlaps Among Diseases 119mentioning
confidence: 99%
“…Mutations in their corresponding genes are associated with Usher syndrome type I and nonsyndromic hearing loss (Bolz et al, 2001;Ahmed et al, 2003Ahmed et al, , 2006Schultz et al, 2011). Several interactions between these and other Usher proteins have been described (Reiners et al, 2006;Zallocchi et al, 2010Zallocchi et al, , 2012aCaberlotto et al, 2011).…”
Section: Clarin-1 Interaction With the Mechanotransduction Machinerymentioning
confidence: 99%